Low temperature exerts protective effects by inhibiting mitochondria-mediated apoptosis pathway following pressure injury to rat muscle - Wenyu Zhang; Ran Miao; Jingping Tang; Qingqing Su; Peifeng Li; Hongying Pi (SciELO, 2021)
ABSTRACT Objective: We aimed to determine the effect of different low-temperature range interventions at different time-points in a rat model of pressure injury (PI) produced by Ischemia/Reperfusion (I/R) injury. Methods: Sprague-Dawley rats were randomly assigned to blank control, injury control, and temperature intervention groups. Rats in the injury control and temperature intervention groups (involving exposure to different temperature range at different time-points) were subjected to three cycles of I/R injury with 2-h ischemia and 0.5-h reperfusion to induce PI. Results: The muscle tissues exhibited degenerative changes after compression. Low temperature intervention of 16-18°C in the ischemia period resulted in the lowest degree of tissue damage and significantly decreased levels of Bcl-2-associated X protein (Bax), caspase-9, and caspase-3. Moreover, it resulted in the highest expression level of B-cell lymphoma 2 (Bcl-2) and lowest expression levels of Bax, caspase-9, and caspase-3 in muscle tissues among all intervention groups. Conclusion: Low-temperature intervention at 16-18°C during the ischemia period showed optimal effects on the expressions of apoptotic factors during the development of PI with I/R-induced tissue damage.